Memorials of Richard H. Richardson, D.D (Anson D.F. Randolph and Co., 1893)
Biographical sketch -- The Chicago pastorate -- The Newburyport pastorate -- The Trenton pastorate -- Funeral services and public tributes -- Letters of sympathy -- Sermons by Dr. Richard H. Richardson.